Towards Specialized Translator Studies in a Minority-Language Context: The Multiple Lives and Times of Uya Pawan, Hero of Language Development - Sterk, Darryl (TTR, 2025)
Although scholars had been interested in translators’ agency since the 1990s, Andrew Chesterman introduced new terminology when he proposed an “agent model” for “Translator Studies” in 2009. While subsequent studies have shed light on the agency of literary translators, specialized translators have remained in the shadows, including in minority translation studies. This article is a case study of Uya Pawan, a specialized translator who translates ethnobotanical descriptions between Chinese, the majority language of Taiwan, and Sediq, a critically endangered Indigenous minority language spoken in central Formosa. In settler states around the world, in a race against time, heroic minority-language translators like Uya are translating specialized texts to develop ancestral tongues. As a hero of language development through specialized translation, Uya is an agent par excellence. But an agent model for translator studies must be complemented by a structural interpretation of why, what, and how a translator is translating, and with what effect. While Reine Meylaerts conducted such an analysis within a neo-Bourdieusian framework, this article adopts the framework of Anthony Giddens, whose structuration theory better accommodates a heroic view of linguistic history. There are different ways of being a linguistic hero; Uya’s leads not to purism, but rather, surprisingly, to compromise with the majority language.